Continuing Education and the RNO Journal - Marietta Stanton (Online Journal of Rural Nursing and Health Care, 2012)
Over the past several years we have tried periodically to provide contact hours to all of our readers and constituents through the online RNO journal. This has primarily been accomplished through questions that can be completed after reading a selected article in the journal and then submitting those completed questions to RNO. All of the materials are available within the journal and can be completed electronically or faxed/mailed to RNO. After the questions are received, corrected and processed, a certificate of completion delineating contact hours is sent to the individual. This activity has had a very poor response from readers and after three attempts, it is time to reevaluate this practice and consider other options. This was supposed to generate revenue for RNO but without any respondents it has been a complete failure. Therefore, in the interest of attempting to not only increase revenue as well as provide educational opportunities, it is time to reassess needs. It may be content that is a problem. It also may be cost.